Uterine rupture after previous caesarean section with hysterotomy above the lower uterine segment: Prelabour uterine rupture and placenta previa - Dellino, Miriam; Crupano, Francesco Maria; He , Xuemin; Malvasi, Antonio; Vimercati, Antonella (Acta Biomedica Atenei Parmensis, 2022)
ABSTRACTBackgroundSpontaneous uterine rupture is a severe pregnancy complication. Several risk factors have beendescribed, especially for women with a previous caesarean section.MethodWe reported two cases of uterine rupture (UR) occurring outside of labour in patients with a historyof caesarean section (CS) due to placenta previa.Results: The current study evaluates how a higher hysterotomy, combined with some risk factors,can increase the prevalence of UR in the subsequent pregnancy.ConclusionThis study supports that a careful evaluation of risk factors can identify patients who need a specificfollow up to early diagnose and treat UR and thus improve the maternal-fetal outcome.